2007
DOI: 10.2527/jas.2006-482
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding Salmonella enterica serovar Typhimurium or serovar Choleraesuis on growth performance and circulating insulin-like growth factor-I, tumor necrosis factor-α, and interleukin-1β in weaned pigs1

Abstract: The most common Salmonella serovars causing clinical disease in pigs are Salmonella enterica serovars Typhimurium (Typhimurium) and Choleraesuis. Given that the swine host-adapted serovar Choleraesuis has been reported to cause systemic disease, a different disease outcome from that of Typhimurium, our working hypothesis was that this serovar would likely engage systemic immune-inflammatory mechanisms, resulting in elevated systemic cytokine secretion. Forty-eight weaned pigs were blocked by BW and sex, and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 15 publications
5
12
0
6
Order By: Relevance
“…Clearly, all these measures were affected adversely by repeated oral exposure of pigs to Choleraesuis. In contrast, none of these measures was affected by repeated exposure of pigs to Typhimurium (current report; Fraser et al, 2007). Although we expected Typhimurium to disrupt ADFI, and thereby potentially reduce BW, the oral dose of Typhimurium used in the study was small relative to oral doses reported to provoke enteric disease (Schwartz, 1999) and relative to those we have used previously (Balaji et al, 2000;Turner et al, 2002a,b).…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Clearly, all these measures were affected adversely by repeated oral exposure of pigs to Choleraesuis. In contrast, none of these measures was affected by repeated exposure of pigs to Typhimurium (current report; Fraser et al, 2007). Although we expected Typhimurium to disrupt ADFI, and thereby potentially reduce BW, the oral dose of Typhimurium used in the study was small relative to oral doses reported to provoke enteric disease (Schwartz, 1999) and relative to those we have used previously (Balaji et al, 2000;Turner et al, 2002a,b).…”
Section: Discussionmentioning
confidence: 62%
“…It is of interest to note that in the companion study conducted with pen mates of pigs from the current study, Choleraesuis challenge was not associated with increased circulating tumor necrosis factor-α or IL-1β (Fraser et al, 2007). However, it is important to note that local production of inflammatory cytokines not measured in the current study may be of greater importance and more reflective of local regulation of skeletal muscle growth than systemic cytokines (reviewed in Gabler and Spurlock, 2008).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations